Accuracy of an UWB-based position tracking system used for time-motion analyses in game sports - Leser, R.; Schleindlhuber, A.; Lyons, K.; Baca, A. (European Journal of Sport Science, 2014)
The main aim of this study was to determine the accuracy of the ultra-wideband (UWB)-based positioning system Ubisense, which is used for time-motion analysis in sports. Furthermore, some alternatives for positioning the system's transponders on the atheletes, as well as the accuracy depending on the location of measurement, were tested. Therefore, in a pre-study, some basic issues were examined (measurement assumptions and consistency and location of the system's transponder used for position detection), and position measurements at the borders and in the centre of a basketball field were performed. In the main study, 13 male basketball players (15.8 years ± 0.6; 187.9 height ± 3.4; 77.5 weight ± 3.7), equipped with a Ubisense transponder mounted on top of their heads, handled a trundle wheel during simulated match play. The players with the trundle wheel participated passively in the match by following one of the ten competing players. The distance measurements of the trundle wheel were used as reference values and compared to the Ubisense distance estimations. Best results were found with the measurements of a single mounted transponder on top of the athlete's heads. No differences were detectable in the accuracy between measurements in the centre and at the borders of the basketball field. The (Ubisense) system's difference to the (trundle wheel) reference was 3.45 ± 1.99%, resulting in 95% limits of agreement of -0.46-7.35%. The study indicates the examined system's sufficient accuracy for time-motion analysis in basketball.